2,6-Bis(5,6-dipropyl-1,2,4-triazin-3-yl)-pyridine: structures of An(III) and Ln(III) 1:3 complexes and selectivity - Banik, Nidhu Lal; Denecke, Melissa Anne; Geist, Andreas; Modolo, Giuseppe; Panak, Petra; Rothe, Jörg (Inorganic chemistry communications, 2013)
In continuation of previous studies, 1:3 complexes between Sm(III), Dy(III), Ho(III) or Tm(III) and 2,6-bis(5,6-dipropyl-1,2,4-triazin-3-yl)-pyridine (n-Pr-BTP) are prepared and their coordination structure in solution characterised by means of extended X-ray absorption fine structure (EXAFS). In addition, distribution ratios DM(III) for the extraction of Np(III), Cf(III) and Pm(III) are determined and compared to those for Pu(III), Am(III), Cm(III) and the other Ln(III).